A Modular Approach to Phosphoglycosyltransferase Inhibitors Inspired by Nucleoside Antibiotics. Issue 11 (10th December 2015) - Walvoort, Marthe T. C.; Lukose, Vinita; Imperiali, Barbara
Abstract: Phosphoglycosyltransferases (PGTs) represent "gatekeeper" enzymes in complex glycan assembly pathways by catalyzing transfer of a phosphosugar from an activated nucleotide diphosphosugar to a membrane‐resident polyprenol phosphate. The unique structures of selected nucleoside antibiotics, such as tunicamycin and mureidomycin A, which are known to inhibit comparable biochemical transformations, are exploited as the foundation for the development of modular synthetic inhibitors of PGTs. Herein we present the design, synthesis, and biochemical evaluation of two readily manipulatable modular scaffolds as inhibitors of monotopic bacterial PGTs. Selected compounds show IC50 values down to the 40 μm range, thereby serving as lead compounds for future development of selective and effective inhibitors of diverse PGTs of biological and medicinal interest. Abstract : Inspired by the functional characteristics of mureidomycin A and tunicamycin, two novel scaffolds are synthesized that display low‐micromolar IC50 against the monotopic phosphoglycosyltransferase PglC (see scheme).